Translation Problems of Some Specific Words in the Story “Bemor” by A. Qahhor - Zafar, Allayev (Research Parks Publishing LLC, 2024)
This article describes discusses the translation problems on the work of Abdulla Kahhar named “Patient” and propose alternative variant based on the theory and practice of translation.